2017
DOI: 10.1038/s41598-017-14289-w
|View full text |Cite
|
Sign up to set email alerts
|

ALK and IGF-1R as independent targets in crizotinib resistant lung cancer

Abstract: ALK positive non-small cell lung cancer is highly responsive to ALK inhibitors such as crizotinib, but drug resistance typically develops within a year of treatment. In this study we investigated whether IGF-1R is an independent druggable target in ALK-positive lung cancer cells. We confirmed that combination ALK and IGF-1R inhibitor treatment is synergistically cytotoxic to ALK-positive lung cancer cells and that this remains the case for at least 12 days after initial exposure to crizotinib. ALK-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“… 16 As reported, IGF-1R overexpression can be found in many types of cancers, such as colorectal cancer and lung cancer. 22 24 A couple of reports identified that inhibition of IGF-1R exerts anti-tumor effects, therefore, IGF-1R has been suggested as a novel therapeutic target for GC patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 16 As reported, IGF-1R overexpression can be found in many types of cancers, such as colorectal cancer and lung cancer. 22 24 A couple of reports identified that inhibition of IGF-1R exerts anti-tumor effects, therefore, IGF-1R has been suggested as a novel therapeutic target for GC patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib-resistant (CR-H3122) cells were generated as described in Wilson et al . 35 and were maintained in 0.8 µM of crizotinib. Briefly, H3122 cells were cultured with increasing concentrations of crizotinib starting from 0.4 µM for 24 h followed by 0.56 µM for next 24 h. Cells were then maintained in 0.80 µM from 3 rd day to 4 months.…”
Section: Methodsmentioning
confidence: 99%
“…Increased activation of other HER family members beyond EGFR, including HER2 and HER3 may also mediate acquired resistance to crizotinib [ 59 ]. In addition, upregulation of IGF1R signaling has been recently identified as an important bypass pathway, and blockade of IGF1R activity resensitized crizotinib resistant cells to ALK inhibition in pre-clinical models [ 60 , 61 ]. Finally, amplification of KIT also represents a potential mechanism of crizotinib resistance, though increased expression of KIT alone does not appear to be sufficient to confer resistance [ 51 ].…”
Section: Introductionmentioning
confidence: 99%